2021
DOI: 10.3390/s21113581
|View full text |Cite
|
Sign up to set email alerts
|

Empiric Unsupervised Drifts Correction Method of Electrochemical Sensors for in Field Nitrogen Dioxide Monitoring

Abstract: This paper investigates the long term drift phenomenon affecting electrochemical sensors used in real environmental conditions to monitor the nitrogen dioxide concentration [NO2]. Electrochemical sensors are low-cost gas sensors able to detect pollutant gas at part per billion level and may be employed to enhance the air quality monitoring networks. However, they suffer from many forms of drift caused by climatic parameter variations, interfering gases and aging. Therefore, they require frequent, expensive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…evaluated the performance of a four electrodes electrochemical sensor for in-field nitrogen dioxide monitoring and also proposed an empirical unsupervised recalibration method. This study revealed the effectiveness of the proposed drift correction approach [37].…”
Section: Electrochemical Gas Sensorsmentioning
confidence: 65%
“…evaluated the performance of a four electrodes electrochemical sensor for in-field nitrogen dioxide monitoring and also proposed an empirical unsupervised recalibration method. This study revealed the effectiveness of the proposed drift correction approach [37].…”
Section: Electrochemical Gas Sensorsmentioning
confidence: 65%
“…Alphasense NO 2 (NO2-B43F) sensors are popular, low-cost sensors for measuring the concentration of nitrogen dioxide in the ambient air using the electrochemical method (4-electrodes). The working principle of the NO 2 electrochemical sensor is based on electrochemical reactions [ 5 ]. When the air passes through, it creates a reaction in the electrochemical cell.…”
Section: Methodsmentioning
confidence: 99%
“…Europe’s most problematic pollutants in terms of health are PM, NO 2 , and ground-level O 3 [ 4 ]. Nitrogen dioxide (NO 2 ) is one of the major pollutant gases, and its emanation is mainly caused by traffic [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the process error of electrochemical sensor fabrication, there are certain differences in the sensitivity and baseline drift of each sensor. In order to make the monitoring results more accurate, the sensor should be necessarily calibrated for a more accurate sensitivity and zero voltage [ 36 ]. The reaction basis of the electrochemical sensors is a chemical reaction, the response of which is easily affected by temperature changes, thereby resulting in output drift in the case of climate changes throughout the year.…”
Section: Methodsmentioning
confidence: 99%